2001
DOI: 10.1159/000048698
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic Heterotypic Sprouting in the Unilaterally Dopamine-Depleted Mouse Neostriatum

Abstract: The effects of unilateral 6-hydroxydopamine (6-OHDA) treatment on striatal serotonin neurons in 12-day-old mice were studied using immunohistochemistry. The unilateral 6-OHDA lesions were evaluated with tyrosine hydroxylase (TH) immunohistochemistry. The majority of the TH-immunoreactive structures disappeared from the substantia nigra and neostriatum on the 6-OHDA lesioned side. However, the density of serotonin fibers was markedly increased throughout the 6-OHDA-depleted neostriatum 1 year later. These resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…This interpretation is supported by the stronger 5-HT labeling observed in the striatal functional territories of recovered monkeys and weaker labeling observed in monkeys with stable motor symptoms than in normal monkeys (Mounayar et al, 2007). This serotoninergic hyperinnervation, often observed in animal models of PD (Zhou et al, 1991;Gaspar et al, 1993;Yamazoe et al, 2001), may be compensatory. Indeed, 5-HT may promote DA release from the remaining dopaminergic fibers (Benloucif and Galloway, 1991;Yadid et al, 1994).…”
Section: Relevance Of Repeated Microdialysis For Investigating Neurocmentioning
confidence: 89%
See 1 more Smart Citation
“…This interpretation is supported by the stronger 5-HT labeling observed in the striatal functional territories of recovered monkeys and weaker labeling observed in monkeys with stable motor symptoms than in normal monkeys (Mounayar et al, 2007). This serotoninergic hyperinnervation, often observed in animal models of PD (Zhou et al, 1991;Gaspar et al, 1993;Yamazoe et al, 2001), may be compensatory. Indeed, 5-HT may promote DA release from the remaining dopaminergic fibers (Benloucif and Galloway, 1991;Yadid et al, 1994).…”
Section: Relevance Of Repeated Microdialysis For Investigating Neurocmentioning
confidence: 89%
“…We observed an increase in 5-HT concentration which was greater in the sensorimotor than in the associative-limbic striatum. Ultrastructural studies on 6-OHDA rats (Zhou et al, 1991), MPTP mice (Yamazoe et al, 2001), and MPTP monkeys (Gaspar et al, 1993) have demonstrated that nigrostriatal dopaminergic pathway destruction leads to serotoninergic hyperinnervation of the striatum. These data are consistent with our neurochemical findings and with the negative correlation between TH-positive fiber counts and 5-HT levels in the associative-limbic striatum.…”
Section: Modifications Associated With Motor Symptom Expressionmentioning
confidence: 99%
“…In several studies in which mouse pups were injected with 6-OHDA, no mention was made about death or reduced body weight in these pups [Shimizu et al, 1987;Fink et al, 1992;Yamazoe et al, 2001]. Their research focus and protocols differed from those presented here, and perhaps they did not notice the stunted growth.…”
Section: Resultsmentioning
confidence: 79%
“…Some authors have suggested that removing DA neurons in neonates provides an opportunity for regenerative mechanisms, particularly among monoaminergic neurons [Björklund et al, 1981;Zigmond and Stricker, 1985;Takeuchi et al, 1991]. For example, it has been reported that neuronal systems containing serotonin further extend their processes into areas otherwise occupied by DA terminals [Imamoto et al, 1980;Stachowiak et al, 1984;Berger et al, 1985;Snyder et al, 1986;Yamazoe et al, 2001]. It is also possible that DA signaling by the remaining neurons is more efficient when lesions 532 Dev Neurosci 2002;24:531-538 Brot/Szczypka/Reavell/Marck/Matsumoto/ Palmiter occur while the dopaminergic system is still developing [Bruno et al, 1987].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, axon sprouting of serotonin fibers appears in the striatum of the experimental animals and generates a markedly dense distribution. These findings suggest that the serotonin neuron system has a strong influence on the dopamine neuron system (Yamazoe, 2001). This phenomenon, called "heterotypic sprouting", is observed particularly between the serotonin neuron and dopamine neuron systems.…”
Section: High Sprouting Capabilitymentioning
confidence: 93%